Obesity and risk for respiratory diseases: a Mendelian randomization study - Yang, Wenwen; Yang, Yanjiang; Guo, Yan; Guo, Jinde; Ma, Minjie; Han, Biao (Frontiers in Endocrinology, 2023)
Background No existing comprehensive Mendelian randomization studies have focused on how obesity affects respiratory diseases. Methods BMI and waist circumference, mainly from the UK Biobank, and 35 respiratory diseases from the FinnGen Biobank were subjected to Mendelian randomization analyses. In this study, the inverse variance weighting method was used as the predominant analysis method and was complemented by MR-Egger and weighted median methods. Horizontal pleiotropy and potential outliers were detected by employing the MR-PRESSO method. Results: This study indicated that obesity rises the possibility of acute upper respiratory infections (BMI: OR=1.131, p<0.0001; WC: OR=1.097, p=0.00406), acute sinusitis (BMI: OR=1.161, p=0.000262; WC: OR=1.209, p=0.000263), acute pharyngitis (WC: OR=1.238, p=0.0258), acute laryngitis and tracheitis (BMI: OR=1.202, p=0.0288; WC: OR=1.381, p=0.00192), all influenza (BMI: OR=1.243, p=0.000235; WC: OR=1.206, p=0.0119), viral pneumonia (WC: OR=1.446, p=0.000870), all pneumoniae (BMI: OR=1.174, p <0.0001; WC: OR=1.272, p <0.0001), bacterial pneumoniae (BMI: OR=1.183, p=0.000290; WC: OR=1.274, p<0.0001), acute bronchitis (BMI: OR=1.252, p <0.0001; WC: OR=1.237, p=0.000268), acute unspecified lower respiratory infection (BMI: OR=1.303, p=0.000403), chronic tonsils and adenoids diseases (BMI: OR=1.236, p <0.0001; WC: OR=1.178, p=0.000157), chronic laryngotracheitis and laryngitis (WC: OR=1.300, p=0.00785), COPD (BMI: OR=1.429, p <0.0001; WC: OR=1.591, p <0.0001), asthma (BMI: OR=1.358, p <0.0001; WC: OR=1.515, p <0.0001), necrotic and suppurative conditions of lower respiratory tract (WC: OR=1.405, p=0.0427), pleural effusion (BMI: OR=1.277, p=0.00225; WC: OR=1.561, p<0.0001), pleural plaque (BMI: OR=1.245, p=0.0312), other diseases of the respiratory system (BMI: OR=1.448, p <0.0001; WC: OR=1.590, p <0.0001), and non-small cell lung cancer (BMI: OR=1.262, p=0.00576; WC: OR=1.398, p=0.00181). This study also indicated that obesity decreases the possibility of bronchiectasis (BMI: OR=0.705; p=0.00200). Conclusion: This study revealed that obesity increases the risk of the majority of respiratory diseases (including 20 of all 35 respiratory diseases) and that obesity decreases the risk of bronchiectasis.